2022
DOI: 10.1108/k-12-2021-1250
|View full text |Cite
|
Sign up to set email alerts
|

Positive reframing as a mediator between gratitude and technostress amongst Indian students during the COVID-19 pandemic

Abstract: PurposeThe aim of the current study was to examine the previously unexplored relationship between positive reframing as a mediator between gratitude and technostress in Indian students. By examining this relationship, the authors aim to expand the theoretical domain of gratitude research by examining its potential influence on technology-induced stress.Design/methodology/approachA cross-sectional survey was used to collect and analyze data from 552 Indian college students who participated in graduate and postg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…A few other studies have demonstrated that gratitude interventions have consistent associations with improved psychological well-being including increased life satisfaction, mood, happiness and positive affect (Dickens, 2017; Portocarrero et al , 2020; Watkins et al , 2014). Gratitude induces positive reframing, which in turn reduces technostress among Indian students (Garg et al , 2022).…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…A few other studies have demonstrated that gratitude interventions have consistent associations with improved psychological well-being including increased life satisfaction, mood, happiness and positive affect (Dickens, 2017; Portocarrero et al , 2020; Watkins et al , 2014). Gratitude induces positive reframing, which in turn reduces technostress among Indian students (Garg et al , 2022).…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…Although the pandemic coronavirus disease 2019 (COVID-19) has created havoc around the world, one rare silver lining is that it accelerated the rate of technology adoption. With strict lockdowns, online classes and work-from-home, both momentum and penetration of digital technologies have risen exponentially in the last two years (De' et al, 2020;Garg et al, 2022). This sudden spike in digital technologies has renewed the interest of researchers and practitioners in understanding and navigating users' online behavior.…”
Section: Introductionmentioning
confidence: 99%
“…With strict lockdowns, online classes and work-from-home, both momentum and penetration of digital technologies have risen exponentially in the last two years (De’ et al. , 2020; Garg et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Biggins & Holley (2022) have also highlighted that during the pandemic, college students experienced technostress because they viewed that the faculty members were lack of technological competence and exhibited less empathy for their students. Under the same circumstance, a study conducted by Garg et al (2023) indicated that students' gratitude can be a determining factor in the reduction of technostress, implying that they will experience technostress when they do not show positive acceptance towards technology.…”
Section: Introductionmentioning
confidence: 99%